2012
DOI: 10.1002/ccd.24312
|View full text |Cite
|
Sign up to set email alerts
|

A completely fractured zotarolimus‐eluting stent in an aortocoronary saphenous vein bypass graft

Abstract: Drug-eluting stents (DES) have significantly improved the rate of target vessel revascularization in comparison with bare metal stents. DES fracture was not reported in multicenter randomized clinical trials, but several case reports of DES fracture have been published, mostly with sirolimus-eluting stents. DES fracture is associated with stent restenosis and thrombosis. We report a zotarolimus-eluting stent fracture in an aortocoronary saphenous vein graft (SVG) bypass. The patient presented with chest pain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“… 12 There are only a few case reports on ZES fracture in the literature. Venero et al 13 reported a ZES fracture in an aortocoronary saphenous vein bypass graft (SVG). Recently, Lee et al 14 described two cases of ZES fracture: one was detected with intravascular ultrasound (IVUS) and the other with conventional coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“… 12 There are only a few case reports on ZES fracture in the literature. Venero et al 13 reported a ZES fracture in an aortocoronary saphenous vein bypass graft (SVG). Recently, Lee et al 14 described two cases of ZES fracture: one was detected with intravascular ultrasound (IVUS) and the other with conventional coronary angiography.…”
Section: Discussionmentioning
confidence: 99%
“…This further strengthens the argument that native complex coronary artery PCI should be the prioritized treatment for SVG failure. There have been some case reports suggesting that the excess DES restenosis rate in SVGs may be related to the excessive curvature and/or mobility of DES during cardiac contractions due to the distorted anatomy leading to stent fracture and failure of local drug delivery [ 57 , 58 , 59 ].…”
Section: Stent Choice In Svg Lesionsmentioning
confidence: 99%